Technology Entrepreneurship (ENT 600) IConstTab / Muhammad Taufiq Abdullah Suhimi … [et al.] - Abdullah Suhimi, Muhammad Taufiq; Ismail, Rahayu; Roslan, Nurul Nasihah; Raja Shuhaimi, Raja Anis Amira; Azmi, Nuraida (2018)
After initial observation towards the tablet offered in the market, the team had chosen a product that we believe can contribute to the Quantity Surveyor and other construction parties. Our product is I Const tablet. Nowadays, quantity surveyors are required to do their work quickly(time saving) and perform the job everywhere(flexible) .I Const tablet provide various tools for quantity surveyors to do their measurement of construction works without attending office. I Const tablet are lighter and user friendly (easy to carry anywhere).This product are created for quality surveyor and other construction parties including for academic purposes.